2020 IEEE International Conference on Image Processing (ICIP) 2020
DOI: 10.1109/icip40778.2020.9190916
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Detection From Raw Circumpapillary OCT Images Using Fully Convolutional Neural Networks

Abstract: Nowadays, glaucoma is the leading cause of blindness worldwide. We propose in this paper two different deep-learningbased approaches to address glaucoma detection just from raw circumpapillary OCT images. The first one is based on the development of convolutional neural networks (CNNs) trained from scratch. The second one lies in fine-tuning some of the most common state-of-the-art CNNs architectures. The experiments were performed on a private database composed of 93 glaucomatous and 156 normal B-scans around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…A recent review of the literature found that most of the deep learning-focused studies using B-scans are conducted in a combination of fundus images to detect glaucoma via RNFL probability maps [42][43][44]. To fill this gap in the literature, we previously proposed different hand-driven and data-driven learning strategies for glaucoma diagnosis in [20,41,45], whose outcomes support the basis of this paper.…”
Section: Related Worksupporting
confidence: 54%
“…A recent review of the literature found that most of the deep learning-focused studies using B-scans are conducted in a combination of fundus images to detect glaucoma via RNFL probability maps [42][43][44]. To fill this gap in the literature, we previously proposed different hand-driven and data-driven learning strategies for glaucoma diagnosis in [20,41,45], whose outcomes support the basis of this paper.…”
Section: Related Worksupporting
confidence: 54%
“…A number of studies have developed approaches based upon convolutional neural networks (CNNs) to detect glaucoma from optical coherence tomography (OCT) images. 6 10 These studies, in general, show excellent performance in terms of reasonably high sensitivity and specificity. However, to demonstrate clinical usefulness, it is essential to test a deep learning system's ability to be effective with a new dataset from a different clinic.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to the presented learning strategy, we propose several architectural changes that improve over existing ones both quantitatively and from an interpretability perspective. In our recent works focused on glaucoma detection from raw OCT samples [7]- [9], we conducted an in-depth experimental analysis of different deep-learning architectures, both trained from scratch and fine-tuning the most popular models in the literature. Specifically, the VGG family of networks reported the best results in [7].…”
Section: B Proposed Architecturementioning
confidence: 99%
“…In our recent works focused on glaucoma detection from raw OCT samples [7]- [9], we conducted an in-depth experimental analysis of different deep-learning architectures, both trained from scratch and fine-tuning the most popular models in the literature. Specifically, the VGG family of networks reported the best results in [7]. So, in [9], we employed them as a strong backbone to develop a new feature extractor able to learn useful representations from the slides of a spectraldomain (SD)-OCT volume.…”
Section: B Proposed Architecturementioning
confidence: 99%
See 1 more Smart Citation